1998
DOI: 10.1111/j.1469-7793.1998.647bg.x
|View full text |Cite
|
Sign up to set email alerts
|

Lanthanum‐mediated modification of GABAA receptor deactivation, desensitization and inhibitory synaptic currents in rat cerebellar neurons

Abstract: We investigated La3+ effects on recombinant and native γ‐aminobutyric acid A (GABAA) receptors using rapid agonist applications and on inhibitory synaptic currents (IPSCs) in granule and stellate neurons of rat cerebellar slices. Rapid desensitization of currents elicited by 200 ms pulses of 1 mM GABA to small lifted cells transfected with α1β3γ2 cDNAs was greatly decreased by the coapplication of 100 μm LaCl3. GABA responses were unaffected when coapplication lasted only 2 ms. In contrast, with LaCl3 pre‐perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 37 publications
0
21
0
Order By: Relevance
“…In addition, the maximal THIP-gated current was greater than the maximal GABA-gated current following 48 h steroid treatment, another unique pharmacological characteristic of α4[6]βδ GABAR (Brown et al, 2002) but not other GABAR subunit combinations, where THIP is a partial GABA agonist. In addition, La 3+ produced a nearly complete inhibition of THIP-generated current following steroid treatment, which is also characteristic of α4[6]βδ GABAR (Brown et al, 2002;Saxena et al, 1997;Zhu et al, 1998). Although La 3+ effects are not known at all GABAR subtypes, potent inhibition by La 3+ is not observed at α1βδ, α1βγ2 or α4βγ2 subtypes (Brown et al, 2002;Saxena et al, 1997;Zhu et al, 1998), and thus allows us to partially distinguish between these receptor subtypes.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…In addition, the maximal THIP-gated current was greater than the maximal GABA-gated current following 48 h steroid treatment, another unique pharmacological characteristic of α4[6]βδ GABAR (Brown et al, 2002) but not other GABAR subunit combinations, where THIP is a partial GABA agonist. In addition, La 3+ produced a nearly complete inhibition of THIP-generated current following steroid treatment, which is also characteristic of α4[6]βδ GABAR (Brown et al, 2002;Saxena et al, 1997;Zhu et al, 1998). Although La 3+ effects are not known at all GABAR subtypes, potent inhibition by La 3+ is not observed at α1βδ, α1βγ2 or α4βγ2 subtypes (Brown et al, 2002;Saxena et al, 1997;Zhu et al, 1998), and thus allows us to partially distinguish between these receptor subtypes.…”
Section: Discussionmentioning
confidence: 93%
“…In addition, La 3+ produced a nearly complete inhibition of THIP-generated current following steroid treatment, which is also characteristic of α4[6]βδ GABAR (Brown et al, 2002;Saxena et al, 1997;Zhu et al, 1998). Although La 3+ effects are not known at all GABAR subtypes, potent inhibition by La 3+ is not observed at α1βδ, α1βγ2 or α4βγ2 subtypes (Brown et al, 2002;Saxena et al, 1997;Zhu et al, 1998), and thus allows us to partially distinguish between these receptor subtypes. We have reported (Sundstrom-Poromaa et al, 2002) similar pharmacological characteristics of CA1 hippocampal pyramidal cells after withdrawal from P, when α4βδ GABAR expression is increased in hippocampus.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…These findings are characteristic of increased expression of α4βδ GABAR, for which gaboxadol produces a greater maximal current than GABA and which are nearly completely inhibited by La 3+ (Brown et al, 2002). In contrast, most other receptors are either unaffected or potentiated by La 3+ (Saxena et al, 1997;Zhu et al, 1998). The increased response of native GABAR to 1-3 mM ethanol after short-term steroid treatment in the present study is nearly identical to what we have observed in recombinant α4β2δ receptors as well as following steroid withdrawal (Sundstrom-Poromaa et al, 2002), when hippocampal α4βδ GABAR expression is increased.…”
Section: Discussionmentioning
confidence: 79%